Determinants of Firm Value in Indonesia’s Consumer Cyclical Sector: A Signaling Theory Approach - Zahira Bunga Firdhausy; Arum Pujiastuti; Shofiatul Mila (JOB: Journal of Organizational Behavior, 2025)
This study aims to determine the effect of internal and external company factors on firm value from the perspective of Signalling Theory. Firm value in this study is measured using proxies such as Price to Book Value (PBV) and Tobin’s Q. The internal factors examined include Capital Structure using the Debt to Equity Ratio (DER), Company Growth using Growth, and Accounting Conservatism using Earning/Accrual Measures. Meanwhile, the external factors include Audit Quality with a Dummy Variable, and Foreign Ownership measured by the percentage of shares held by foreign parties relative to total outstanding shares. The sample was selected using a purposive sampling method with criteria of consumer cyclical sector companies that issued complete annual reports from 2018 to 2022 and were listed at least since 2018, resulting in 69 companies. The findings indicate that Capital Structure positively affects PBV, while Company Growth and Accounting Conservatism have no significant effect on PBV. Audit Quality and Foreign Ownership also show no effect on PBV. For Tobin’s Q, Accounting Conservatism has a negative impact, while Capital Structure, Company Growth, Audit Quality, and Foreign Ownership do not show significant effects